Contribution of diet and physical activity to metabolic parameters among survivors of childhood leukemia. - Tonorezos ES; Robien K; Eshelman-Kent D; Moskowitz CS; Church TS; Ross R; Oeffinger KC; Tonorezos, Emily S; Robien, Kim; Eshelman-Kent, Debra; Moskowitz, Chaya S; Church, Timothy S; et al. (Cancer Causes & Control, 2013)
Purpose: Determine the relationship between diet and metabolic abnormalities among adult survivors of childhood acute lymphoblastic leukemia (ALL).Methods: We surveyed 117 adult survivors of childhood ALL using the Harvard Food Frequency Questionnaire. Physical activity energy expenditure (PAEE) was measured with the SenseWear Pro2 Armband. Insulin resistance was estimated using the Homeostasis Model for Insulin Resistance (HOMA-IR). Visceral and subcutaneous adiposity were measured by abdominal CT. Adherence to a Mediterranean diet pattern was calculated using the index developed by Trichopoulou. Subjects were compared using multivariate analysis adjusted for age and gender.Results: Greater adherence to a Mediterranean diet pattern was associated with lower visceral adiposity (p = 0.07), subcutaneous adiposity (p < 0.001), waist circumference (p = 0.005), and body mass index (p = 0.04). For each point higher on the Mediterranean Diet Score, the odds of having the metabolic syndrome fell by 31 % (OR 0.69; 95 % CI 0.50, 0.94; p = 0.019). Higher dairy intake was associated with higher HOMA-IR (p = 0.014), but other individual components of the Mediterranean diet, such as low intake of meat or high intake of fruits and vegetables, were not significant. PAEE was not independently associated with metabolic outcomes, although higher PAEE was associated with lower body mass index.Conclusions: Adherence to a Mediterranean diet pattern was associated with better metabolic and anthropometric parameters in this cross-sectional study of ALL survivors.